Does fear of movement mediate the relationship between pain intensity and disability in patients following whiplash injury? A prospective longitudinal study - Kamper, Steven J.; Maher, Christopher G.; Menezes Costa, Luciola da C.; McAuley, James H.; Hush, Julia M.; Sterling, Michele (Pain (Amsterdam), 2012)
In a cohort of patients with whiplash injuries, fear avoidance partially mediated the relationship between pain soon after injury and disability 3 months later. The aim of this study was to test the capacity of the Fear Avoidance Model to explain the relationship between pain and disability in patients with whiplash-associated disorders. Using the method of Baron and Kenny [1], we assessed the mediating effect of fear of movement on the cross-sectional and longitudinal relationships between pain and disability. Two hundred and five subjects with neck pain due to a motor vehicle accident provided pain intensity (0 to 10 numerical rating scale), fear of movement (Tampa Scale of Kinesiophobia and Pictorial Fear of Activity Scale) and disability (Neck Disability Index) scores within 4 weeks of their accident, after 3 months, and after 6 months. The analyses were consistent with the Fear Avoidance Model mediating approximately 20% to 40% of the relationship between pain and disability. Contrary to our initial hypothesis, the proportion of the total effect of pain on disability that was mediated by fear of movement did not substantially change as increasing time elapsed after the accident. The proportion mediated was slightly higher when fear of movement was measured by Tampa Scale of Kinesiophobia as compared with Pictorial Fear of Activity Scale. The findings of this study suggest that the Fear Avoidance Model plays a role in explaining a moderate proportion of the relationship between pain and disability after whiplash injury.